Plea for a "United States of India" - Hegde, Ramakrishna
In this article author pleads for a comprehensive review of the present distorted relationship between the Centre and the State. It is suggested that such a review should be undertaken by a body established in full consultation with the states so that is commands their confidence and the recommendations must be implemented promptly
Keywords: United States of India; India; Federal State Relation; Centre State Relation; Federal-State Relations - India